Analisa Efisiensi Bank Syariah Indonesia (BSI) Sebelum dan Sesudah Merger - Ahmad Rizal; Rifki Ismal; Indra Indra (Department Islamic Economics, 2023)
The aim of this reserach is measuring the level of efficiency, identifying the level of efficiency and comparing the level of efficiency before and after the merger as well as formulating steps and strategies to increase the efficiency of PT Bank Syariah Indonesia Tbk. The research uses Data Envelopment Analysis (DEA) and T-Test methods, the analysis period is 2015 to February 2021 (Before the Merger) and March 2021 to December 2022 (After the Merger) and the sample in this research is a large-scale Sharia Commercial Bank nationally registered with the Financial Services Authority (OJK). The research results show that based on the VRS assumption, Bank Syariah Indonesia (BSI) obtained the highest average efficiency score with a value of 0.897 compared to Sharia Commercial Banks (BUS) in Indonesia. Meanwhile, BSI's efficiency level experienced a stable efficiency level reaching optimum efficiency from the period 2015 to 2022. Meanwhile, based on CRS assumptions, BSI's efficiency level tended to move steadily from 2015-2020, then experienced an increase from 2021-2022. And the results of the T test show that the significance value is 0.067 or greater than 0.05. This means that it can be concluded that there is no real (significant) difference between the level of efficiency of PT Bank Syariah Indonesia, Tbk before and after the merger. The Potential Improvement at PT Bank Syariah Indonesia, Tbk after the merger is to increase the amount of financing provided by 52%, while operational income is increased by 48%.